Social Capital as a Predictor of Substance Misuse Relapse: Findings from a Case-Control Study - Ali Solaimani; Abdolvahab Baghbanian; Mohammad Amin Behmanesh; Aziz Kassani (Journal of Health Sciences and Surveillance System)
Background: Relapse during substance misuse treatment is common and poses a significant public health challenge. A variety of personal, social, and psychological factors influence it. This study explored the relationship between patients’ social capital, individual traits, and the risk of relapse.Methods: In this case-control study, 218 relapsed patients (case group, n=109) were compared with 109 abstentious patients (control group, n=109) in the four voluntary outpatient addiction treatment centers and one maintenance addiction treatment center using random cluster sampling in Dezful City, Iran, 2020. The data were obtained from structured interviews to determine personal traits, including age, marital status, familysize, education level, job status, type of substance, smoking, and addiction history in the family. A standard social capital questionnaire was used to assess the participants’ personality. Chi-square test, t-test, and logistic regression were used for data analysis.Results: All patients were male, aged between 16 and 68 years, with a mean age of 36.84±6.76 years. The three dimensions of social capital —individual trust (OR=0.33, CI=0.11-0.51), cohesion/social support (OR=0.27, CI=0.07-0.48), and social trust/ associative relations (OR=0.65, CI=0.32-0.92) —are significantly associated with substance misuse relapse. In addition, age (OR=0.85, CI=0.65-0.91), educational level of illiterate/ academic (OR=2.87, CI=1.05-4.18), job status, unemployed/employed (OR=1.39, CI=1.11-1.80), and type of drugs (OR=2.71, CI=1.70- 3.73) had a direct association with substance misuse relapse.Conclusion: The association between social elements and the recurrence of substance misuse in patients receiving Methadone Maintenance Treatment (MMT) is of importance. This study showed that reduced levels of social capital were associated with a higher chance of relapse. To address this issue, it is suggested to introduce inclusive social assistance initiatives that focus on nurturing the community and promoting inclusion among MMT patients.